Market Potential and Border Effects in Europe - Michael Pfaffermayr; Peter Huber; Yvonne Wolfmayr (Austrian Institute of Economic Research (WIFO), 2004)
We estimate a linear approximation of the market potential function derived in geography and trade models. Using a spatial econometric estimation approach, border effects can be identified by a differential impact of neighboring regions' purchasing power, depending on whether two regions are located in (i) the same country (ii) within the EU15 or (iii) outside the EU15. Our results suggest that there are substantial market potential effects on nominal wage rates. We also find significant border effects between EU15 and non-EU15 countries. Our estimation results suggests that the enlargement of the EU on May 2004 may lead to pronounced wage effects in the new member states, but to relatively small ones for the existing members.
Keywords: F10; R12; F12; C21; 330; Market Potential; Border Effects; Spatial Econometrics; Grenze; Kaufkraft; Raumstruktur; Schätzung; EU-Staaten; Marktgröße